PENGARUH LEVERAGE KEUANGAN DAN DIVIDEN TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Abdullah Abdullah; Sutarti Uno (AkMen JURNAL ILMIAH, 2014)
The title of this paper was discussed at the date of December 21, 2013 and has been approved to do research on the Indonesia Stock Exchange Road AP. Petarani 18 A-14 Makassar. The time used for this study is 1 (one) month. The purpose of the research conducted by the authors was to determine the effect of financial leverage and dividends on stock returns in Indonesia Stock Exchange. Object of this study is the stock return on the pharmaceutical group in the Indonesia Stock Exchange in which the data used are secondary data from existing quantitative data on Capital Market Information Center makassar. Which lies in the way the AP Pettarani 18 A-4, Makassar. So the method of analysis using Multiple Linear Regression Analysis, Test F, Test T and Test Assumptions Classic (Normality Test, Test Mulitikolinieri). The results showed that simultaneous, the leverage ratio is Debt to Equity Ratio (DER) and the dividend is Dividend Payout Ratio (DPR) positive and significant effect on stock returns in the pharmaceutical sector manufacturing companies in Indonesia Stock Exchange. But partially, debt-to-equity ratio (DER) a significant positive effect on stock returns, while the dividend payout ratio (DPR) no significant negative effect on stock returns in the pharmaceutical sector manufacturing companies in Indonesia Stock Exchange.Thus, in analyzing, otherwise investors also pay attention to other factors. And of the two variables that have been tested, DER is the variable most dominant influence on stock returns